Modulation of peptide release from single identified Aplysia neurons in culture - Whim, MD (J Neurosci, 1992)
Aplysia neurons B1 and B2 contain large amounts of the neuropeptides SCPA and SCPB. When grown in culture, individual B1 and B2 cells incorporate 35S-methionine into the SCPs, which can be released in a stimulus- and calcium-dependent fashion (Lloyd et al., 1986). We now show that single cells can be stimulated in a manner to evoke release of the SCPs that declines only slightly with repeated stimulation. This has allowed us to examine the ability of several physiologically relevant agonists to modulate the stimulus-evoked release of the SCPs. Bath application of either FMRFamide or 5-HT resulted in a significant decrease in the amount of SCPs released by intracellular stimulation of B1 or B2. The action of 5-HT was dose dependent with an inhibition of release of approximately 70% at a concentration of 100 microM. SCPA did not significantly affect release. The bath application of several compounds that are expected to elevate intracellular levels of cAMP were also found to depress release. To investigate the possibility that the agonists inhibited the release of the SCPs via a hyperpolarization of membrane potential (and perhaps a loss of spikes in the neurites), we examined the actions of 5-HT, FMRFamide, and SCPA on several electrophysiological parameters intended to monitor the level of cell excitability. Surprisingly, even though 5-HT depressed the release of the SCPs from both cells, it depolarized and increased the excitability of B1, and hyperpolarized and decreased the excitability of B2. Furthermore, in contrast to the effects seen in culture, 5-HT depolarized both B1 and B2 in situ.(ABSTRACT TRUNCATED AT 250 WORDS)